Non-involuting congenital hemangioma with delayed hypertrophy: A case series. (June 2022) - Konanur, Anisha; Jimenez, Joaquin E.; Kochin, Megan; McCormick, Andrew; Salgado, Claudia; Yilmaz, Sabri; Bykowski, Michael; Padia, Reema
Abstract: Background: Noninvoluting congenital hemangiomas (NICH) are rare and poorly understood vascular tumors that are present at birth, characterized by lack of growth after birth and lack of involution. We report uncharacteristic cases of NICH hypertrophy occurring later in life. Methods: This is a case series describing the clinical presentation, management, and histologic characteristics of two cases of NICH hypertrophy. Results: Two patients with a NICH of the scalp experienced lesion hypertrophy in teenage or early adult life. Case 1 is a 14-year-old female who presented with a flat left parietal scalp lesion that at first grew slowly with the patient; however, over the span of months grew substantially resulting in an exophytic lesion. The patient had the lesion surgically excised. Case 2 is a 26-year-old female with NICH of left occipital scalp and posterior neck who noted new nodules on the inferior border of the lesion. MRA/MRI showed extension into the occipital calvarium, level V of the neck, and paraspinal musculature. The patient elected to observe given the extent of the lesion and her minimal symptoms. Conclusion: Although postnatal growth of NICH have been described, cases usually occur during the pre-adolescent period where growth is usually proportional to overall growth of the patient. This study describes two cases of rapid onset NICH hypertrophy occurring later in life. Knowledge of the potential for delayed hypertrophy may lead families to seek earlier intervention or opt for more definitive interventions. Additionally, recognition of these variable distinctions will contribute to a better understanding of CH and its various subtypes. Highlights: NICH may have a risk of hypertrophy later in life. Surgical excision is an option for patients and depending on the extent of the lesion.